Improving the transparency of algorithmic management in platform work: The role of the Platform Work Directive - Rosin, Annika; Parviainen, Henni (SAGE Publications, 2026)
Automated decision-making (ADM) and monitoring are central features of platform work and undoubtedly shape platform workers’ working conditions. Yet, platform workers are often unaware of how they are monitored, how their actions inﬂuence working conditions, and on what basis and how the decisions affecting them are made. Increasing the transparency of ADM and monitoring systems can raise the awareness of platform workers and allegedly improve their working conditions.
The Platform Work Directive (PWD) seeks to improve platform workers’ conditions by strengthening their rights to transparency in ADM and monitoring. However, it remains uncertain whether the PWD offers a substantive advancement over existing legal frameworks. This article examines whether the PWD enhances the transparency of algorithmic management in platform work and thereby improves the position of platform workers. We compare the transparency regulation in the PWD with the relevant provisions in the General Data Protection Regulation, the Platform to Business Regulation, the Transparent and Predictable Working Conditions Directive and the Artiﬁcial Intelligence Act.
We conclude that the PWD clearly contributes to the improvement of the transparency rights of platform workers. The personal and material scope of the PWD’s transparency rights is broader than that of the other instruments, as it covers all platform workers, regardless of their actual employment status, and extends to both ADM and monitoring. The transparency obligations imposed on platforms under the PWD are also broader and more clearly deﬁned than those in the other instruments examined in this article.